Forming Limits Prediction of Laminated SUS430/Al1050/SUS430 Composites and the Effect of Component Properties on Mechanical Performance - Li, Xin; Liu, Chunguo; Zhang, Mingzhe (Advanced engineering materials, 2024)
In this study, a constitutive model applied to predict the tensile properties and fracture behavior of well‐bonded multilayered metal composites is extended. The equivalent single‐layer model, as a convenient method, is introduced into finite‐element simulations by combining it with an improved Xue–Wierzbicki damage plasticity model that considers material anisotropy. The steel use stainless (SUS) 430/Al1050/SUS430 laminated sheet fabricated by cold rolling is selected as the research material. The quasistatic uniaxial tests and Nakazima tests are operated to verify the accuracy of the proposed method. The mean errors in tensile stress and fracture forming limit strains are 2% and 3%, respectively. A load‐sharing mixture rule is proposed to assess the effects of the volume fraction, strength coefficient, and hardening exponent of the constituent materials on the mechanical properties of the laminates. In the results, it is indicated that the laminate exhibits sufficient elongation and remains markedly enhanced in tensile strength, reaching 470 Mpa when the ductile Al layer is combined with the higher strength and hardenability steel layer. In this research, it is aimed to clarify the formability characteristics in laminated composites for optimal sheet configuration design and development. A modified Xue–Wierzbicki damage model accounting for material anisotropy is integrated into finite‐element simulations using the equivalent single‐layer model to predict the forming limits of laminated SUS430/Al1050/SUS430 sheets. Additionally, a load‐sharing mixture rule is proposed to analyze the flow behavior in laminates. A good agreement between the proposed methods and experimental works is observed.